2016
DOI: 10.1186/s40798-016-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects on Cardiorespiratory and Metabolic Status After a Concurrent Strength and Endurance Training Program in Diabetes Patients — a Randomized Controlled Trial

Abstract: BackgroundConcurrent aerobic and resistance training (CART) programs have been widely recommended as an important strategy to improve physiologic and functional performance in patients with chronic diseases. However, the impact of a personalized CART program in patients with type 2 diabetes (T2D) requires investigation. Therefore, the primary aim of the current study is to investigate the impact of CART programs on metabolic profile, glycemic control, and exercise capacity in patients with diabetes.MethodsWe e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 64 publications
1
26
0
2
Order By: Relevance
“…In parallel with previous finding, Glut 4 level increase with resistance and weight training specially when performed with main muscle groups. Increased insulin sensitivity and glut 4 (a shortcut to glucose transportation system toward muscle tissues) may be helpful in glucose balance and blood glucose monitoring in a diabetic subject; a fact which was found in our study [12][13][14][15][16][17][18]. Regarding fat loss exercises, there are various types of exercise plans in the world [19].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In parallel with previous finding, Glut 4 level increase with resistance and weight training specially when performed with main muscle groups. Increased insulin sensitivity and glut 4 (a shortcut to glucose transportation system toward muscle tissues) may be helpful in glucose balance and blood glucose monitoring in a diabetic subject; a fact which was found in our study [12][13][14][15][16][17][18]. Regarding fat loss exercises, there are various types of exercise plans in the world [19].…”
Section: Discussionmentioning
confidence: 77%
“…It is the procedure of exercise plan which makes significant changes in physiological parameters. This procedure must be monitored by an exercise physiologist to lead to target weight and normal physiological status [14][15][16][17][18]. The results of presented case study report demonstrated the main roles of intricate mechanisms inside the field of sport science regarding diet plan and exercise programme.…”
Section: Discussionmentioning
confidence: 99%
“…This is a single arm clinical study, an analysis of secondary data from Bassi et al 2 , which was registered in the Brazilian Registry of Clinical Trials (protocol RBR-492q8z). In addition, the study procedures were approved by the Research Ethics Committee of the University Center of Araraquara (protocol 1318/11).…”
Section: Designmentioning
confidence: 99%
“…Additionally, combined training has shown positive results for glycemic control, as seen by HbA1c analysis 2,8 . However, it is known that hyperglycemic peaks experienced on a day to day basis and between physical training sessions have been strongly associated with the development of diabetes complications 9 , regardless of the values of fasting glycemia and HbA1c 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation